2009
DOI: 10.2478/v10042-009-0044-9
|View full text |Cite
|
Sign up to set email alerts
|

BAC-FISH assays delineate complex chromosomal rearrangements in a case of post-Chernobyl childhood thyroid cancer.

Abstract: Structural chromosome aberrations are known hallmarks of many solid tumors. In the papillary form of thyroid cancer (PTC), for example, activation of the receptor tyrosine kinase (RTK) genes, RET and neurotrophic tyrosine kinase receptor type I (NTRK1) by intra-and interchromosomal rearrangements has been suggested as a cause of the disease. However, many phenotypically similar tumors do not carry an activated RET or NTRK-1 gene or express abnormal ret or NTRK-1 transcripts. Thus, we hypothesize that other cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…2A), the cell line S48TK had shown numerous translocations among them several complex translocations including two marker chromosomes, m1 and m2, that carried chromosome 9 derived material (6, 20, 22). Our SKY analysis suggested that m1 is the product of a t(7;9;15), while m2 might have been the results of insertion of chromosome 9 material into a der(8)t(8;15) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…2A), the cell line S48TK had shown numerous translocations among them several complex translocations including two marker chromosomes, m1 and m2, that carried chromosome 9 derived material (6, 20, 22). Our SKY analysis suggested that m1 is the product of a t(7;9;15), while m2 might have been the results of insertion of chromosome 9 material into a der(8)t(8;15) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A preliminary molecular cytogenetic analysis of rearrangements involving the long arm of chromosome 1 in cell line S48TK has been published recently (20). Hybridization of BAC probes that bound either proximal or distal of the two candidate genes NTRK1 and TPM3 could demonstrate two marker chromosomes, one that appear to carry an inversion of the critical region between 144 Mbp and 155 Mbp, while the second marker chromosome showed hybridization pattern indicative of multiple copies of the same region (20). Further fine mapping and delineation of the chromosome 1-specific breakpoints has been initiated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunohistochemistry has gained a leading role in tumour typing and prognostication (Kwan et al 2009;Sun et al 2014;Huber et al 2014). Numerous protein targets are currently available for a multitude of different tumours.…”
Section: Introductionmentioning
confidence: 99%